Diraasat Nahwiyyat 'an Usluub al-Isytighaal Fii al-Qur'aan al-Kariimi wa Tadhmiinuhaa Fii Ta'liim al-Nahwi - Agus Tricahyo; Farid Khoirul Muntaha (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2023)
أما أهداف هذا البحث فهي لمعرفة آية احتوت أسلوب الاشتغال في السور المدنية من القرآن الكريم، ولمعرفة أحكام استعمال أسلوب الاشتغال في السور المدنية من القرآن الكريم، ولمعرفة استفادة هذه الدراسة التحليلية عن أسلوب الاشتغال في تعليم النحو. ومدخل هذا البحث هو بحث كيفي. ونوعه بحث مكتبي. وبياناته آيات من السور المدنية التي احتوت أسلوب الاشتغال. وأسلوب جمع هذه البيانات بمنهج الوثائق. وأسلوب تحليلها بتحليل المحتوى. ونتيجة هذا البحث، أولا إن الآيات التي احتوت أسلوب الاشتغال في السور المدنية هي ست آيات. وهي البقرة: 48، 86، 150، 211؛ آل عمران: 56، 57. ثانيا إن أحكام استعمال أسلوب الاشتغال في السور المدنية هي ثلاثة أحكام. إحداها ترجيح الرفع، وهو في آيتين آل عمران: 56، 57. وثانيتها وجوب الرفع، وهو في آيتين البقرة: 48، 86. وثالثتها ترجيح النصب، وهو في آيتين البقرة: 150، 211. ثالثا إن استفادة الدراسة التحليلية عن أسلوب الاشتغال في تعليم النحو. ينبغي أن يذكر أسباب الاسم السابق، لماذا قُرِأ الاسم السابق بالرفع أو بالنصب، إما وجوبا، وإما جوازا مع الترجيح في أحدهما. وعندما تُعْلَم تلك الأسباب، قُدِّمَتِ الأمثلة التي تشبه بأحكام الاشتغال في تلك الآيات المحلَّلة. وهذه الطريقة تسمى بالاقتباس عند الاصطلاحات البلاغية، وبالطريقة القياسية عند الاصطلاحات التعليمية. Abstract This study aims to find out a verse that contains the method of working in the civil surahs of the Holy Qur’an, to know the provisions for using the method of working in the civil surahs of the Holy Qur’an, and to know the benefit of this analytical study on the method of working in teaching grammar. The method is qualitative research. Its type is desk research. Furthermore, his statements are verses from the civil surahs that contain the method of working. The method of collecting this data is the documentation method. Moreover, the method of analyzing it is by analyzing the content. As a result of this research, first, six verses contain the method of working in the civil suras. Al-Baqarah: 48, 86, 150, 211; Al-Imran: 56, 57. Secondly, the rules for using the working method in civil suras are three. One of them is the weighting of the noun in two verses of Al Imran: 56, 57. The second is the obligation of the noun, which is in the two verses of Al-Baqarah: 48, 86. Furthermore, the third is the weighting of the accusative in the two verses of Al-Baqara: 150, 211. Thirdly, the benefit of the analytical study on the method of engaging in teaching syntax. He should mention the reasons for the previous noun, why the previous noun was read in the noun or accusative, Either obligatory or permissible, with weighting in one of them. Furthermore, when those reasons are known, examples are presented that resemble the rulings of preoccupation in those analyzed verses. This method is called quotation in rhetorical conventions and the standard method in educational conventions.